2017
DOI: 10.1039/c6nr08470b
|View full text |Cite
|
Sign up to set email alerts
|

Thin TiOxlayer as a voltage divider layer located at the quasi-Ohmic junction in the Pt/Ta2O5/Ta resistance switching memory

Abstract: TaO has been an appealing contender for the resistance switching random access memory (ReRAM). The resistance switching (RS) in this material is induced by the repeated formation and rupture of the conducting filaments (CFs) in the oxide layer, which are accompanied by the almost inevitable randomness of the switching parameters. In this work, a 1 to 2 nm-thick Ti layer was deposited on the 10 nm-thick TaO RS layer, which greatly improved the RS performances, including the much-improved switching uniformity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…To improve the switching uniformity, we herein propose a new simple methodology of constructing cone-shaped CFs in unipolar RRAM cells, by replacing the conventional inert Pt cathode with the chemically active Ta cathode (① in Figure b). The key is to take advantage of the spontaneous redox reaction at the Ta/Ta 2 O 5 interface (precisely, the out-diffusion of oxygen ions from Ta 2 O 5 into Ta) to generate an interfacial layer containing a large amount of oxygen vacancies and/or tantalum suboxides. , This interfacial layer will act as a load resistor and thus prevent the overgrowth of CFs during forming and set processes through the voltage divider effect. , Also, the Ta electrode itself with a higher resistivity than the Pt electrode can contribute to such a voltage divider effect. Kim et al have demonstrated the growth of CFs from the cathode to the anode , and, more importantly, the gradual evolution of CFs’ shape from conical to cylindrical as their overall size increases. , Therefore, because of the prevention of overgrowth by the interfacial layer and the Ta electrode itself, a more cone-like CF denoted as CF 3 (② in Figure b) is expected to grow from the Ta TE to the Pt BE and then short-circuit the electrode pair in Ta/Ta 2 O 5 /Pt RRAM cells during forming with the Pt BE positively biased with respect to the Ta TE.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the switching uniformity, we herein propose a new simple methodology of constructing cone-shaped CFs in unipolar RRAM cells, by replacing the conventional inert Pt cathode with the chemically active Ta cathode (① in Figure b). The key is to take advantage of the spontaneous redox reaction at the Ta/Ta 2 O 5 interface (precisely, the out-diffusion of oxygen ions from Ta 2 O 5 into Ta) to generate an interfacial layer containing a large amount of oxygen vacancies and/or tantalum suboxides. , This interfacial layer will act as a load resistor and thus prevent the overgrowth of CFs during forming and set processes through the voltage divider effect. , Also, the Ta electrode itself with a higher resistivity than the Pt electrode can contribute to such a voltage divider effect. Kim et al have demonstrated the growth of CFs from the cathode to the anode , and, more importantly, the gradual evolution of CFs’ shape from conical to cylindrical as their overall size increases. , Therefore, because of the prevention of overgrowth by the interfacial layer and the Ta electrode itself, a more cone-like CF denoted as CF 3 (② in Figure b) is expected to grow from the Ta TE to the Pt BE and then short-circuit the electrode pair in Ta/Ta 2 O 5 /Pt RRAM cells during forming with the Pt BE positively biased with respect to the Ta TE.…”
Section: Resultsmentioning
confidence: 99%
“…A compliance current ( I cc ) of 1 mA was applied on the samples to avoid hard breakdown and to improve the RS performance. 24 It is well known that the formation/rupture of V O CF is widely recognized as the switching mechanism in the transition metal oxides. 4,25 Compared with Device 1 and Device 3, Device 2 exhibited good reproducibility, which may be correlated with the appropriate oxygen vacancy concentration in the HfO x layer.…”
Section: Resultsmentioning
confidence: 99%
“…A proper load resistor serially connected with memristor has been reported to improve the switching uniformity and endurance of the memristor. [ 29–31 ] The value of R is set to R=RH·RL$R = \sqrt {{R_{\rm{H}}} \cdot {R_{\rm{L}}}} $ which depends on the memristors parameters. The resistance state ( R out ) of M 2 and the voltage value of the output of the comparator ( R out ) both stand for the result of logic calculation in reading mode.…”
Section: Resultsmentioning
confidence: 99%